2016
DOI: 10.1111/ajt.13596
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Medications and Squamous Cell Skin Carcinoma: Nested Case-Control Study Within the Skin Cancer after Organ Transplant (SCOT) Cohort

Abstract: Organ transplant recipients (OTR) have a substantially elevated risk of squamous cell skin carcinoma (SCSC), largely attributed to immunosuppressive medications used to prevent graft rejection, although data to support the role of newer drugs on SCSC risk are sparse. We investigated the association between immunosuppressive medications and SCSC risk among cardiac and renal transplant recipients in the SCOT cohort study. Incident cases were ascertained through medical record review after self-report of skin bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 59 publications
1
86
0
1
Order By: Relevance
“…Similarly, azathioprine has been associated with NMSC not only in the renal transplant recipients where it is used concomitantly with CNIs (4) but also when used alone for the treatment of Inflammatory bowel disease (38, 39). In accord with our findings, a recent case-control study of kidney and heart transplant recipients reported that azathioprine, but not MMF, was associated with increased risk of NMSC, and that the association was independent of CNIs (40). In the current study, we also noted a lower risk of NMSC in patients who received sirolimus-based regimens at discharge compared to a reference regimen based in tacrolimus and MMF; however, sirolimus was not associated with differences in the risk of viral-linked or other cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, azathioprine has been associated with NMSC not only in the renal transplant recipients where it is used concomitantly with CNIs (4) but also when used alone for the treatment of Inflammatory bowel disease (38, 39). In accord with our findings, a recent case-control study of kidney and heart transplant recipients reported that azathioprine, but not MMF, was associated with increased risk of NMSC, and that the association was independent of CNIs (40). In the current study, we also noted a lower risk of NMSC in patients who received sirolimus-based regimens at discharge compared to a reference regimen based in tacrolimus and MMF; however, sirolimus was not associated with differences in the risk of viral-linked or other cancers.…”
Section: Discussionsupporting
confidence: 92%
“…A recent large study of cardiac and renal transplant patients demonstrated a lower risk of squamous cell carcinoma in patients receiving mycophenolate (OR 0.45, 95% CI 0.29‐0.69) compared with those treated with azathioprine (OR 2.67 95% CI 1.23‐5.76) …”
Section: Review Criteriamentioning
confidence: 99%
“…36 In contrast, one meta-analysis of kidney and kidney-pancreas transplant recipients demonstrated a significantly reduced risk of any malignancy with use of the mammalian target of rapamycin (mTOR) inhibitor, sirolimus (adjusted hazard ratio [aHR] 0.60, 95% CI 0.39-0.93), although this was driven by keratinocyte carcinomas as well. 3,38,39 Data on the direct effect of specific immunosuppressants on gynecologic, including oncogenic virus-related, cancers is sparse and often conflicting. 3,38,39 Data on the direct effect of specific immunosuppressants on gynecologic, including oncogenic virus-related, cancers is sparse and often conflicting.…”
Section: Role Of Immunosuppressantsmentioning
confidence: 99%
“…37 Mycophenolate has also been potentially associated with lower cancer rates, perhaps because of its activity against an enzyme, inosine monophosphate dehydrogenase, that is expressed at high levels in some solid tumors. 3,38,39 Data on the direct effect of specific immunosuppressants on gynecologic, including oncogenic virus-related, cancers is sparse and often conflicting. A registry study in the United States reported variable results with different immunosuppressants.…”
Section: Role Of Immunosuppressantsmentioning
confidence: 99%